Pengaruh Penambahan Silika Abu Kelapa Sawit pada Batako Agropolimer - Prendika, Wimpy; Syafei, Dedri; Nasirly, Riri (ALKIMIA, 2021)
This research was conducted to provide more value to oil palm ash and decrease the use of cement in agropolymer brick making. Oil palm industrial biomass waste contains silica (SiO2) which can replace the silica content in cement. This study aims to determine the chemical composition of oil palm biomass ash, physical and mechanical properties and surface morphology of agropolymer bricks. Agropolymer brick made from cement: sand (1:4) with variations palm ash 0; 4,3; 8.6; 12.9; 17.2; and 21.5% which has been purified with 3% HCl and a total weight of 7500 g. Agropolymer brick making is done by utilizing palm ash to reduce cement use. XRF test results showed that the greatest composition of ash before and after acidification was SiO2 namely 50.475% to 56.255%. The results of the water absorption test showed that the water absorption capacity of the concrete blocks increased with the addition of silica from the ash from palm biomass. The results of the average density test of concrete blocks with the addition of palm biomass silica were lower than the density of sand, namely 2.241 g/cm3. The compressive strength test results show that formula 3 has the optimum compressive strength is 28.8235294 kg/cm2. These results are supported by the SEM analysis of formula 3 showing that the agglomeration and grain size are not homogeneous and the surface morphology is denser. The brick produced is in accordance with SNI SNI 03-0348-1989 category IV the quality of solid concrete bricks B70.